Preferensi Risiko dalam Memoderasi Pengaruh Pemahaman Peraturan Perpajakan, Sanksi Perpajakan dan Kesadaran Wajib Pajak terhadap Kepatuhan Wajib Pajak - Karina Elsani; Aries Tanno (Politeknik Ganesha Medan, 2023)
Indonesia as a developing country needs to increase the country's economic growth so that it can be on par with other countries. To make it happen, the State of Indonesia requires a sizable source of funds. As quoted from the official website of the Ministry of Finance, it is stated that the MSME sector has a very large contribution to the national economy and has a significant role in tax revenue. This study aims to examine the effect of understanding tax regulations, tax sanctions and taxpayer awareness on taxpayer compliance with risk preference as a moderating variable. Source data of this study is the primary data from online questionnaire shared in electronic by google form. The research sample is the taxpayers of MSME (Micro, Small and Medium Enterprises) registered at the Tax Service Office (TSO) Pratama Padang Dua as much as 99 respondents. Data analysis techniques using SEM model with Warp Partial Least Square (PLS) computer program version 7.0. The results of this study indicate that understanding of tax regulations has a significant negative effect on taxpayer compliance, while tax sanctions have a positive and insignificant effect on taxpayer compliance and taxpayer awareness has a significant positive effect on taxpayer compliance. Besides that, risk preferences cannot moderate the effect of understanding tax regulations on taxpayer compliance. Meanwhile risk preferences are able to moderate the effect of tax sanctions on taxpayer compliance and risk preferences cannot moderate the effect of taxpayer awareness on taxpayer compliance. Keywords: Risk Preference; Tax Sanctions; Taxpayer Awareness; Taxpayer Compliance; Understanding of Tax Regulations